Stratigraphy and geochemistry of Jurassic carbonate rocks from Suha krajina and Mala gora mountain (Southern Slovenia) - Strohmenger, Christian; Dozet, Stevo (Geologija, 1990)
Detailed sedimentological investigations have been carried out in the section Kompolje-Ogorelec at the Mala gora mountain, and in the section Krka-Mali Korinj at Suha krajina about 35 km SSE from Ljubljana (NW Yugoslavia). In both sections a complete sequence of the Jurassic calcareous beds is exposed, including the contacts between the Upper Triassic and the Lower Lias, and the Upper Malm and the Lower Cretaceous. The field studies showed that at least the uppermost part of Dogger was not deposited. The thickness of the Jurassic sequence is about 1500 m. The stratigraphic relationships have been established by means of micro - and macrofossils, and by lithologic comparisions. The interpretation of microfacies has been supplemented by geochemical, micropaleontological and some other analyses. A polymict karst breccia within the Lower Malm beds proves a long lasting emergence of the carbonate platform during the Upper Malm; it is apparently the equivalent of the bauxite horizon commonly developed between the Lower and the Upper Malm in Slovenia. The distribution of trace elements follows the trends implied by the microfacies analyses.